Legal Framework for Protecting Online Business Transactions in Indonesia: A Sharia Economic Law Perspective - Setiadi, Setiadi; Solihin, Dadin; Hasan Ridwan, Ahmad; Kamaludin Yusup , Deni; Hasanuddin, Muhammad (IJBLE Scientific Publications Community Inc., 2025)
This research departs from the limited study of legal protection for online business actors from the perspective of Sharia economic law, even though this issue has a strategic role in the development of the digital economy in Indonesia. The purpose of the research is to analyze the implementation of legal protection, identify obstacles and solutions, examine the integration of Sharia principles in regulations, and explore the prospects of Sharia-based digital legal development. The method used is qualitative with a juridical-normative and descriptive-analytical approach. Data was obtained through literature studies, interviews, observations, and documentation, and then analyzed thematically. The results of the study show that regulations are still fragmented and consumer-oriented, so that the protection of Islamic business actors is not proportional. The challenges that arise include low digital legal literacy, limited legal infrastructure, and disharmony between the DSN-MUI fatwa and national law. The research concludes the need for regulatory reform through legal harmonization, institutional synergy, and the establishment of special regulators. Research contributions include strengthening the legal literature on digital Sharia economics as well as practical recommendations for policymakers.